2019
DOI: 10.1177/0363546519873672
|View full text |Cite
|
Sign up to set email alerts
|

Association of Preoperative Gluteal Muscle Fatty Infiltration With Patient Outcomes in Women After Hip Abductor Tendon Repair Augmented With LARS

Abstract: Background: Hip abductor tendon repair has demonstrated encouraging outcomes. The influence of fatty infiltration (FI) on outcome has not been explored. Purpose: To investigate the association between preoperative hip abductor FI and clinical outcome after hip abductor tendon repair. Study Design: Case series; Level of evidence, 4. Methods: A total of 84 women underwent hip abductor tendon repair. The mean age was 64.6 years (range, 43-84 years); body mass index, 27.7 (range, 20.0-40.2); and duration of sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 46 publications
0
32
0
1
Order By: Relevance
“…The overall mean age (sample size adjusted) was 53.7 years (range, 17-88 years), and the mean body mass index (14 studies ** ) was 28.3 (range, 19.4-40.2). One study excluded male participants 22 ; for the remaining studies, the female-to-male sex ratio was calculated as 7:1. Information on laterality was provided in 7 studies, 9 , 10 , 29 , 33 , 38 , 50 , 53 with 54.3% of left hips treated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The overall mean age (sample size adjusted) was 53.7 years (range, 17-88 years), and the mean body mass index (14 studies ** ) was 28.3 (range, 19.4-40.2). One study excluded male participants 22 ; for the remaining studies, the female-to-male sex ratio was calculated as 7:1. Information on laterality was provided in 7 studies, 9 , 10 , 29 , 33 , 38 , 50 , 53 with 54.3% of left hips treated.…”
Section: Resultsmentioning
confidence: 99%
“…Pain was most commonly assessed using a visual analog scale (VAS; 16 studies ¶¶ ) or numeric rating scale (NRS; 2 studies 10 , 42 , 51 ). Common patient-reported outcome measures (PROMs) were the modified Harris Hip Score (mHHS; 9 studies ## ), Harris Hip Score (HHS; 8 studies 14 , 18 , 21 , 22 , 31 , 38 , 41 , 50 ), Oxford Hip Score (6 studies 8 , 9 , 17 , 21 , 22 , 31 ), 12-Item Short Form Health Survey (SF-12; 5 studies 4 , 21 , 22 , 31 , 50 ), Hip Outcome Score (HOS; 4 studies 29 , 37 , 40 , 50 ), global rating of change scale (4 studies 21 , 22 , 31 , 42 ), 36-Item Short Form Health Survey (SF-36; 3 studies 8 , 9 , 17 ), and Patient Acceptable Symptom State (3 studies 4 , 25 , 26 ). Rarely used measures for the determination of outcomes were the Lower Extremity Functional Scale, 10 , 18 Nonarthritic Hip Score, 29 , 53 and Merle D’Aubigné–Postel score 17 , ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the patients demonstrated significant improvement in pain, gait, strength, and subjective outcomes at a minimum of 2-year follow-up. 23 In patients undergoing abductor tendon suture-anchor repair augmented with a transosseous synthetic scaffold (LARS; Corin Group, Cirencester Cloucestershire, UK), Ebert et al 20,24 reported significant improvement in all mean patient PROs and clinical scores, including hip abductor strength and gait performance in 142 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have since replicated these results and shown improvement with surgical repair in various types of hip abductor pathology. 12,17,36,38,45 To the best of our knowledge, no previous studies have evaluated risk factors for the presence of hip abductor tears in patients undergoing hip arthroscopy.…”
mentioning
confidence: 99%